International Propagation of Business Cycles - Polak, J. J. (Review of Economic Studies, 1939)
Journal Article International Propagation of Business Cycles Get access J. J. Polak J. J. Polak Geneva Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 2, February 1939, Pages 79–99, https://doi.org/10.2307/2967392 Published: 01 February 1939